O peixe boi da Amazônia no baixo Javari, AM - Brasil: conhecimento local, uso de habitat e conservação - PANTOJA, Tatyanna Mariucha de Araujo (Universidade Federal do Pará, 2017)
Trichechus inunguis plays an important role in food webs and dynamics of water bodies where it lives. It’s ecological importance has not stopped the species from suffering a intense process of hunting despite the legal protection since the decade of 60. The observation of the occurrence of the species in parts of the Javari and Quixito rivers, near the county of Atalaia do Norte, and the registers of hunting events in the region led this research. The research aimed to carry out a study on aspects of local knowledge, habitat use and conservation of T. inunguis in order to support the definition of strategies for their conservation in the lower Javari region, Amazonas, Brazil. The first chapter aimed to compare local knowledge and documented scientific knowledge of the Amazon Manatee. In order to achieve this, interviews were conducted with riverine residents of Atalaia do Norte municipality, or communities or isolated houses along stretches of the Javari river, Itacoaí and Quixito. 50 interviews were conducted covering topics as morphology, metabolism and age, breathing, feeding and migration, breeding and intraspecific interactions. The content of the Compared Cognition Tables (CCT) resulted in an average adhesion value of 0.6. This result demonstrates that it is possible to recognize in reports and utterances of the study population, the existence of cognitive codes perfectly capable of dialoguing with scientific knowledge, indicating the possibility of collective construction of measures geared toward the conservation of the species. The second chapter aimed to investigate local knowledge on the occurrence sites of the species. For a year a sampling was conducted at excerpts from Javari rivers, Quixito and Itacoaí to investigate the suitability of using this type of knowledge on measures directed to the study of the species in the wild. In addition, the study has looked to investigate the effect of environmental variables related to the occurrence of T. inunguis in the study area. Therefore, we use Generalized Linear Models (GLM) to model the distribution of T. inunguis using presence and absence data in sites located within the study area and its relation with variables of environmental and anthropogenic order. We recognize, based on the observed results, the potential of local knowledge about the occurrence sites (detection success rate of occurrence of the sites listed as of the occurrence of the species evidence was 37.66%, in contrast to 1.43 % of sites listed as non-occurrence of the manatee). Therefore consider their owners as key elements in the development of ecological studies of the species, and that should be incorporated into protective actions to these animals. The variable components of the model built (EVD ~ SIT + LARG + DIST.ATN + COM + EMB1 + FLOR.ALAG) validate its objective basis. Furthermore, the model demonstrates that the methodology is capable of replication in similar cases. Still, recommendations regarding data collection bearing in mind the intrinsic features of each variable analyzed (geographical configuration of the sampled rivers, use that animals do the flooded forest, effect of sightings closest communities) are made to maximize potential the use of explanatory models the occurrence of the species, thereby creating greater biological reliability of results. The third chapter raised the species mortality data and studied the perception of the region bordering population on it’s conservation. Individuals contacted for the first component of the study were applied questions about the animals, their relationships with other species, the mythical body of knowledge about the species, their uses, the risks to which it is subject, and the threat of its extinction. A survey was done (by direct observation, participant or not) on mortality of manatees in the study area, and the various causes of deaths recorded. To analyze the perception we used the Discourse of the Collective Subject (DCS). Mortality data were recorded and analyzed descriptively. Impressions beforehand to the questions were mostly positive (73%), and even the negative (27%) can base discussions on conservation actions regionally. The data on the risks and T. inunguis mortality brings evidence that the hunting of these animals still occurs materially and locally and this is an aspect that requires further studies in this regard. Studies are recommended regarding population ecology and dynamics of species populations in the area, under the action of an additional source of mortality: the hunting factor.